Analisa Manajemen Risiko Pada UMKM Salon Kecantikan Menggunakan Framework ISO 31000 dan Matriks Risiko Manajemen: Studi Kasus “Salon Teh Rani” - Aghnia Yasyfa; Anisa Roshy Rosdian; Hesti Hisani Latifah Hamdah; Almaira Sarah Junjunan; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Beauty salon MSMEs in Indonesia play a vital role in supporting the service sector and the local economy, yet they face various risks that can threaten their business sustainability. This study aims to analyze risk management at Teh Rani Beauty Salon MSME across market, financial, marketing, operational, human resource, and legal aspects. The study employed qualitative methods, including interviews and observations, to obtain data on the salon's conditions and challenges. A SWOT analysis and risk matrix were used to map risk management priorities, enabling business owners to establish appropriate mitigation strategies. The study demonstrates the need for systematic implementation to improve operational efficiency, maintain customer loyalty, and strengthen competitiveness amidst the increasingly fierce competition in the beauty industry.